A Cross-Sectional Study on Teaching Informational Text for Third Graders in Vietnamese School Context - Linh, Vuong Tuyet; János, Steklács (VNU Journal of Science: Education Research, 2024)
Reciprocal teaching method has been proven to be effective for reading comprehension. However, in Vietnam, primary school teachers are still unacquainted with this method. Thus, this study investigated the current situation of teaching and learning informational texts among third grade students in Vietnam in order to highlight the need for reciprocal teaching in the reading comprehension of informational texts. Based on a sample of 272 primary school teachers and their responses on a self-designed survey questionnaire, the teachers still struggle with identifying informational texts and have yet to focus on guiding students to extract the lessons/meanings from the texts and apply them in their daily lives. In this regard, the lack of informational text reading strategies and the limited exposure to the new curriculum may be contributing factors. Meanwhile, the contents of the informational texts were deemed appropriate for the children’s understanding and they helped maintain their interest in finding the main idea of each paragraph. Considering the benefits of reciprocal teaching, future research in Vietnam should explore the application of this method in subjects beyond reading comprehension such as mathematics, science, physics, etc.